2019
DOI: 10.1371/journal.pone.0213271
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nominal photon energies on normal tissue sparing in knowledge-based radiotherapy treatment planning for rectal cancer patients

Abstract: The interactive adjustment of the optimization objectives during the treatment planning process has made it difficult to evaluate the impact of beam quality exclusively in radiotherapy. Without consensus in the published results, the arbitrary selection of photon energies increased the probability of suboptimal plans. This work aims to evaluate the dosimetric impact of various photon energies on the sparing of normal tissues by applying a preconfigured knowledge-based planning (RapidPlan) model to various clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…For this region, classical radiotherapy 27,28 VMAT for RC was also reported as a result with respect to RapidPlan. 21 They clarified that the investigated 10X, 8X, and 6X photons and higher energies provide better normal tissue sparing in RapidPlan. 21 Our findings suggested that higher beam energies were still advantageous in normal tissue sparing for deep-seated tumors of large volumes, even if many beam entries were used, such as in the VMAT technique.…”
Section: Pk Evaluated With Various Energy Types Demonstrated That the Gedmentioning
confidence: 97%
See 3 more Smart Citations
“…For this region, classical radiotherapy 27,28 VMAT for RC was also reported as a result with respect to RapidPlan. 21 They clarified that the investigated 10X, 8X, and 6X photons and higher energies provide better normal tissue sparing in RapidPlan. 21 Our findings suggested that higher beam energies were still advantageous in normal tissue sparing for deep-seated tumors of large volumes, even if many beam entries were used, such as in the VMAT technique.…”
Section: Pk Evaluated With Various Energy Types Demonstrated That the Gedmentioning
confidence: 97%
“…Huang et al mentioned that target parameter in Rapid-Plan models configured for flattened beams cannot optimize unflattened beams without adjustments. 21 However, the authors did not validate to adjust optimization parameters. Castriconi et al mentioned that the validation step can enhance the robustness of the RapidPlan model to reproduce the plans with the same quality.…”
Section: Pk Evaluated With Various Energy Types Demonstrated That the Gedmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, AI-based technology was introduced for automated treatment planning [ [41] , [42] , [43] , [44] , [45] ], showing very promising clinical applications for several treatment sites and technical modalities. Mathematical algorithms for knowledge-based treatment planning and quality assurance with few manual interventions were applied [ [46] , [47] , [48] ] to predict achievable dose distributions for an individual patient’s anatomy and dose prescription based on a database of high-quality treatment plans.…”
Section: Ai In Breast Cancer Rt Planningmentioning
confidence: 99%